Midgut Volvulus Due To Herniation Of The Ileum Into The Right Paraduodenal Recess Following Blunt Abdominal Trauma (Journal of Chittagong Medical College Teachers' Association, 2014)
Midgut volvulus with gangrene is not a rare event. With normal rotation, the mesentery is broad and fixed, but the narrow pedicle formed by the base of the mesentery in malrotation of the gut predisposes the midgut to clockwise twisting from the duodenum to the transverse colon. Excessive length of the mesentery, or a point of adhesion at the convexity of the loop may act as an axis for the loop .The actual inciting mechanism is unknown but various possibilities, including unusual movement of the torso, abnormal intestinal peristalsis, or segmental bowel distention, have been suggested. This is a grave surgical emergency to save the life of the patient. We are reporting a case of midgut volvulus with herniation of the ileum into the right paraduodenal recess after blunt abdominal trauma (BAT). A 8 years old boy complaints of abdominal pain, vomiting, and distension of the abdomen following diving to a pond. Abdominal x-ray and USG, CBC, Serum Electrolyte were carried out to evaluate the child. The patient was first treated conservatively but later on, he deteriorated and needed urgent laparotomy.JCMCTA 2013 ; 24 (2): 40-43